Enhancing English Speaking Skills and Confidence Through Collaborative Speech Activities - De Leon, John Michael; Campoamor-Olegario, Lizamarie (Philippine Journal of Education Studies (formerly the Education Quarterly), 2025)
Although English is taught from Grade 1 to Grade 12 in the Philippine curriculum, many junior high school students still lac k the competence and confidence to speak in English, which can be attributed to their negative experiences and feelings toward using the language. This research investigated the effects of integrating collaborative learning activities into instruction to enhance students’ oral communicative skills and confidence in English. As such, a four-week intervention program was designed using the communicative language teaching (CLT) approach and then implemented among 39 Grade 9 students at a private school in the Philippines. Data were gathered through class observation, a speaking test, video recordings, reflection log entries, and questionnai res. Quantitative and qualitative data analyses revealed improvement in the students’ speaking competence and confidence in using English in different oral activities in the classroom. The findings also showed a positive response from the students on the use and benefits of collaborative learning. The study suggests that collaborative learning helps to create a less-threatening learning environment, facilitates effective and efficient performance of speaking activities in English, and provides various benefits to learners.